Enhancement Effect of Microbubble-Enhanced Ultrasound in Microwave Ablation in Rabbit VX2 Liver Tumors. (23rd January 2020) - Xiao, Shuyi; Hu, Zhiwen; He, Yan; Jin, Hai; Yang, Yuwen; Chen, Liping; Chen, Qiaoli; Luo, Qiong; Liu, Jianhua
Abstract : Objectives . One reason for the high recurrence and metastatic rates of tumors such as hepatocellular carcinoma (HCC) treated by microwave ablation (MWA) is the presence of residual foci in the tumor due to heat sink effect. Microbubble-enhanced ultrasound (MEUS) can noninvasively disrupt and block the tumor blood perfusion and has the potential to overcome the heat sink effect and enhance the therapeutic effect of MWA. The study aimed at evaluating the potential additional benefit of microbubble-enhanced ultrasound (MEUS) in hepatocellular carcinoma (HCC) treated by microwave ablation (MWA). Methods . In this study, a new strategy of combining MWA with MEUS for treating HCC was proposed. Twenty-four rabbits with VX2 tumors in livers were randomly divided into MEUS + MWA, MEUS alone, MWA alone, and blank control groups, respectively ( n = 6). In the MEUS group, the tumors were directly exposed to therapeutic ultrasound for 5 min with a concurrent intravenous injection of microbubbles (0.1 ml/kg diluted into 5 ml saline). In the MWA group, the tumors were treated by MWA for 1 min. In the MEUS + MWA group, tumors were ablated by MWA for 1 min after ultrasound cavitation enhanced by microbubbles as in the MEUS group. In the blank control group, the tumors received probe sham and intravenous saline. Contrast-enhanced ultrasound (CEUS) was performed before treatment and immediately after treatment to display the size, shape, and contour of the tumors. Throughout the treatment process, the local temperature of the treatment area was detected by a temperature needle punctured into the tumor. The blood samples of animals were obtained after treatment for evaluating the liver function. Tumor cell necrosis and apoptotic rates were observed after treatment by histological examination. Results . CEUS showed that although perfusion defects appeared in all the treatment groups, especially in the MEUS + MWA group, there was no significant difference between the two groups on the volumes of perfusion defects, which were 1.78 ± 0.31 (cm 3 ) in the MWA group and 1.84 ± 0.20 (cm 3 ) in the combined group P < 0.01 . The time to reach the peak temperature of the treatment area was 21.7 ± 5.0 (s) in the MWA group and 10.3 ± 5.0 (s) in the MEUS + MWA group P < 0.01 . The peak temperature (PT) of the two groups were 100.9 ± 5.0 (°C) and 134.1 ± 6.0 (°C), respectively P < 0.01 . This showed that the local temperature of the treatment area was sharply increased to a higher PT using MEUS + MWA. Histological examination results showed that the apoptosis rate and necrosis rate in the MEUS + MWA group were 23.6 ± 4.6% and 60.5 ± 9.7%, respectively, which are significantly higher than those in the MWA group (17.9 ± 4.5% and 37.6 ± 3.4%) and those in the MEUS group (18.2 ± 1.0% and 37.6 ± 3.4%). They are all higher than those in the control group (3.85 ± 1.72% and 5.3 ± 1.1%). Hematological examination showed no significant differences between treatment groups on liver function. Conclusions . These results suggested MEUS treatment alone may significantly reduce tumor blood perfusion and led to a sharp rise in the local temperature of the treatment area to a higher PT using MEUS + MWA with higher rates of necrosis and apoptosis of cancer cells without severe liver function damage, which might be a safe strategy for treating HCC.